Gut microbes impact stroke severity via the trimethylamine N-oxide pathway - Zhu, Weifei; Romano, Kymberleigh A.; Li, Lin; Buffa, Jennifer A.; Sangwan, Naseer; Prakash, Prem; Tittle, Aaron N.; Li, Xinmin S.; Fu, Xiaoming; Androjna, Charlie; DiDonato, Anthony J.; Brinson, Kimberly; et al. (Cell host & microbe, 2021)
Clinical studies have demonstrated associations between circulating levels of the gut-microbiota-derived metabolite trimethylamine-N-oxide (TMAO) and stroke incident risk. However, a causal role of gut microbes in stroke has not yet been demonstrated. Herein we show that gut microbes, through dietary choline and TMAO generation, directly impact cerebral infarct size and adverse outcomes following stroke. Fecal microbial transplantation from low- versus high-TMAO-producing human subjects into germ-free mice shows that both TMAO generation and stroke severity are transmissible traits. Furthermore, employing multiple murine stroke models and transplantation of defined microbial communities with genetically engineered human commensals into germ-free mice, we demonstrate that the microbial cutC gene (an enzymatic source of choline-to-TMA transformation) is sufficient to transmit TMA/TMAO production, heighten cerebral infarct size, and lead to functional impairment. We thus reveal that gut microbiota in general, specifically the metaorganismal TMAO pathway, directly contributes to stroke severity. [Display omitted] •Gut microbial transplantation studies show stroke severity is a transmissible trait•The metaorganismal TMAO pathway impacts infarct size and functional impairment•Gut microbial CutC increases host TMAO levels, cerebral infarct size, and functional deficits Zhu et al. demonstrate via gut microbial transplantation studies that stroke severity is transmissible; specifically, the metaorganismal TMAO pathway was found to impact infarct size and functional impairment in mice. Gut microbial CutC increased host TMAO generation, cerebral infarct size, and post-stroke functional deficits.